Personal authenticator on the basis of two-factors: Palmprint features and tokenized random data - Pang, Ying Han; Ngo, David Chek Ling; Teoh, Andrew Ben Jin (Springer Berlin Heidelberg, 2004)
This paper presents a novel two-factor authenticator which hashes tokenized random data and moment based palmprint features to produce a set of private binary string, coined as Discrete-Hashing code. This novel technique requires two factors (random number + authorized biometrics) credentials in order to access the authentication system. Absence of either factor will just handicap the progress of authentication. Besides that, Discrete-Hashing also possesses high discriminatory power, with highly correlated bit strings for intra-class data. Experimental results show that this two-factor authenticator surpasses the classic biometric authenticator in terms of verification rate. Our proposed approach provides a clear separation between genuine and imposter population distributions. This implies that Discrete-Hashing technique allows achievement of zero False Accept Rate (FAR) without jeopardizing the False Reject Rate (FRR) performance, which is hardly possible to conventional biometric systems.